Challenges in first line chemotherapy and targeted therapy in advanced gastric cancer. Issue 8 (August 2014) - Garrido, Marcelo; Fonseca, Paula J; Vieitez, Jose María; Frunza, Madalina; Lacave, Angel J
<x xml:space="preserve">Abstract</x> Chemotherapy prolongs survival in advanced gastric cancer (AGC). The challenges involved in this procedure are providing a framework to aid in determining the best single or combined chemotherapy protocols for targeted agents in front-line therapy for patients in a clinical setting. A review of Phase II-III studies published or referenced in major oncology congress publications from 1970 to 2013 was performed. Cisplatin and fluoropyrimidine remain the reference regimen. Fluoropyrimidine combined with oxaliplatin or irinotecan may also be employed in special situations. There are no comparative studies of the same regimens with or without anthacyclines; thus, the effectiveness of anthacyclines remains under debate. The introduction of trastuzumab in the front-line therapy of HER2-positive patients and ramucirumab in refractory patients ushered in an age of targeted therapy for this disease.